Role of Preemptive Nebulized Lignocaine in Endotracheal Tube Tolerance during General Anesthetic induction and emergence - Rafia Kousar, Muhammad Abdul Aziz, Mehreen Akram, Haq Dad Durrani, Jai Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: General anesthesia is an essential component of anesthesia and endotracheal intubation is a basic step to secure the airway in patients undergoing any surgical procedure. Airway manipulation causes mucosal inflammation resulting in coughing, straining, bucking and subsequent distress to the patient. Aim: To find out whether preemptive use of nebulized lignocaine has some role in endotracheal tube tolerance during General anesthetic induction and emergence. Study design: Randomized control trial Methodology: The randomized controlled study was done on 68 patients scheduled for general surgical procedures.Patients were allocated intoGroup A and Group Bby closed envelope method with 34 patients in each group. In Group A lignocaine 2% (1.5-2mg/kg) with normalsaline 0.9% to prepare total of 5 ml solution, was used to nebulize the patients with face mask connected with O2 at 7L/min and in Group B5ml normal saline 0.9% was used to nebulize the patients for 15minutes. The endotracheal tube tolerance was noted at both intubation and extubation. Results: Endotracheal tube tolerancein Group A was markedly significant than in Group B both during intubation and extubation. In Group A, 32/34(94.12%) patients reflected tolerance to endotracheal tube both during intubation and extubation while in Group B only 06/34(17.65%) reflected tolerance to endotracheal tube both during intubation and extubation. Conclusion: Preemptive nebulized lignocaine suppresses the airway reflexes and significantly improves the endotracheal tube tolerance. Keywords: Endotracheal intubation, extubation, nebulization, lignocaine.